Effects of modified Elkin’s procedure along with specific breech exercises in breech repositioning and to determine the feasibility of normal delivery: an experimental study - Govindan, Sumathi; Vadivel, Shivaranjini Sundara; Gopalakrishnan, Surya; Abraham, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Breech presentation is observed in 3-4% of pregnancies at term and is one of the leading causes of caesarean section. Babies with breech presentation are at increased risk of complications during birth. An experimental study was conducted to demonstrate the effects of the Modified Elkin’s procedure and specific breech exercises. However, there is a lack of evidence suggesting which technique is superior in reducing the risk associated with vaginal delivery in breech presentation. Methods: This experimental study enrolled 123 subjects diagnosed with breech presentation by ultrasonography during the third trimester. Participants in the experimental group were instructed to perform the Modified Elkin’s procedure along with specific breech exercises. These interventions were designed to be safe and simple and were found to significantly aid in breech repositioning, thereby increasing the feasibility of normal delivery. The study duration was 8 months. Treatment consisted of three sessions per week on alternate days for 4 weeks, including rest periods. Exercises were advised for women with fetuses in breech presentation. Results: The results of the study showed a marked difference between the pre- and post-test values. After completing the full set of exercise sessions, there was a significant improvement in breech repositioning and an increased likelihood of normal delivery. Conclusions: This trial revealed that 4 weeks of treatment using the Modified Elkin’s procedure along with specific breech exercises is effective for breech repositioning. Based on the results, this technique appears to be a simple, less painful, and safe option for managing breech presentation in the third trimester of pregnancy. It may also influence the mode of delivery.